ETOS KERJA DAN JIWA KORSA PRAJURIT DALAM PELAKSANAAN TUGAS DAN FUNGSI PADA SATUAN PENDIDIKAN KAPAL SELAM TNI AL DI KODIKLATAL SURABAYA - jurnalmap map; Dias Prawira; Indra Prasetyo; Cathrine Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This study attempts to analyze and describe the work ethic of the korsa (esprit de corps) warrior's soul in carrying out the duties and functions of the Indonesian Navy submarine education unit at Kodiklatal Surabaya. The type of research used in this study is descriptive research. The research suggestions used are qualitative suggestions. The data analysis technique used is descriptive qualitative data analysis techniques. Respect between soldiers and superiors as well as other unit members has been done well. Respectfully agreed upon through good cooperation, upholding the oath of soldiers and Trisillas of the Indonesian Navy and the sultanate of clans. The factor of competition against the army work ethic that is less than optimal is the understanding of soldiers on work ethos in the military environment is still lacking, soldiers lack the ability to develop ethos, still contain less disciplined soldiers as well as an inhibiting factor to develop work ethic in their company. Then as a supporting factor, there is a warrior guide regarding the korsa (esprit de corps) soul continuously. Keywords: work ethic, korsa (esprit de corps) soul, duties and functions